A Rural Next Generation Network (R-NGN) and Its Testbed - Armein Z. R. Langi (LPPM ITB, 2007)
Rural Next Generation Networks (R-NGN) technology allows Internet protocol (IP) based systems to be used in rural areas. This paper reports a testbed of R-NGN that uses low cost Ethernet radio links, combined with media gateways and a softswitch. The network consists of point-to-point IP Ethernet 2.4 GHz wireless link, IP switches and gateways in each community, standard copper wires and telephone sets for users. It uses low power consumption, and suitable for low density users. This combination allows low cost systems as well as multiservices (voice, data, and multimedia) for rural communications. An infrastructure has been deployed in two communities in Cipicung Girang, a village 10 km outside Bandung city, Indonesia. Two towers link the communities with a network of Institut Teknologi Bandung (ITB) campus. In addition, local wirelines connect community houses to the network. Currently there are four houses connected to each community node (for a total of eight house), upon which we can perform various tests and measurements.